2018
DOI: 10.1377/hlthaff.2018.0159
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Participation And Transparency In Biobank Research

Abstract: Medical biobanks often struggle to obtain sustainable funding. Commercialization of specimens is one solution, but disclosure of commercial interests to potential contributors can be dissuasive. Recent revisions to the federal human subjects research regulations will soon mandate such commercialization disclosure in some circumstances, which raises questions about implications for practice. In this nationally representative, probability-based survey sample of the US adult population, we found that 67 percent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 31 publications
1
33
0
1
Order By: Relevance
“…With regard to commercialization, multiple studies have demonstrated concerns over commercialization of biospecimens among the public and potential for this to decrease willingness to contribute to biobanks and to erode public support for biobank research . The literature demonstrates that disclosure of potential for commercial use and transparency can mitigate these concerns, and public support for commercialization can be fostered by independent governance of biobanks and reinvestment of financial support in future research . In our study, participants indicated that use of their biospecimen to develop a new drug or sharing of information with a drug company would generally increase willingness to donate, with less than 20% holding a negative view.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…With regard to commercialization, multiple studies have demonstrated concerns over commercialization of biospecimens among the public and potential for this to decrease willingness to contribute to biobanks and to erode public support for biobank research . The literature demonstrates that disclosure of potential for commercial use and transparency can mitigate these concerns, and public support for commercialization can be fostered by independent governance of biobanks and reinvestment of financial support in future research . In our study, participants indicated that use of their biospecimen to develop a new drug or sharing of information with a drug company would generally increase willingness to donate, with less than 20% holding a negative view.…”
Section: Discussionmentioning
confidence: 81%
“…Prior work has also identified two concerns regarding broad consent for biobanking in the general population: commercialization and the nonwelfare interests of participants. With regard to commercialization, multiple studies have demonstrated concerns over commercialization of biospecimens among the public and potential for this to decrease willingness to contribute to biobanks and to erode public support for biobank research . The literature demonstrates that disclosure of potential for commercial use and transparency can mitigate these concerns, and public support for commercialization can be fostered by independent governance of biobanks and reinvestment of financial support in future research .…”
Section: Discussionmentioning
confidence: 99%
“…31 Crafting clear disclosures-especially about aspects of biobank participation that people may find risky, concerning, unexpected, or unfavorable (such as commercial use of data and public data sharing)-helps promote transparency while providing researchers with an opportunity to build trust with prospective participants. 32 Many issues identified through our interviews have also been documented with English-speaking participants, though other issues may be more specific to the E R H E R H & translation process or to Spanish-speaking populations. Qualitative data captured through cognitive interviews allowed us to identify subtle but important issues with the materials as translated to Spanish.…”
Section: Discussionmentioning
confidence: 99%
“…Those who received the traditional form, for instance, more often perceived specific language to be contradictory (for example, concerning the scope and limits of individual protections). These findings suggest there is a fine line between providing exhaustive detail in the interest of being thorough and overwhelming the primary intended message about the overall level of risk and protections, leading to reduced comprehension and confusion 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation